The impact of experimental forest fire on collembolan communities - Olejniczak, Izabella; Prędecka , Anna; Russel, Stefan (Studia Ecologiae et Bioethicae, 2014)
Our study was carried out in fresh pine mixed forest, Biala Forest, near Warsaw (52°59’ N, 21°46’ E and 52°79’ N, 21°89’ E, Eastern Poland). Three experimental plots, 1m2 size, were chosen at random and burnt in June. The material was collected: just after the experimental fire (in June ), 30, 60, and 90 days after fire (respectively: in July, August, and September). On every sampling occasion 10 soil samples of an area of 10cm2 and a depth of 5 cm were taken in each sampling plots: burnt plots, in the border of burnt plots, and in surroundings of burnt plots. We found that experimental fire influenced on collembolan densities (Kruskall-Wallis test, H=8.29, P=0.01). Just after the experimental fire we found no collembolans in burnt plots. In a period of 90 days following the experimental fire densities of springtails of burnt and surroundings were similar. Euedaphic springtails were the dominating group in burnt plots and contrary to the border of burnt plots and surroundings, we noticed no epigeic springtails. Contribution of epigeic, hemiedaphic and euedaphic species in collembolan communities of investigated areas could point to different defense strategies of these invertebrates. Immature individuals of Collembola were the most numerous in burnt plots and at the border of burnt plots and this phenomenon is probably crucial for the reconstruction of collembolan communities after the fire.